Coaching for wellness: a guide to mental health and substance use prevention in women's aesthetic sports - Nelson, Reese, author; Popichak, Katrina, advisor; Butki, Brian, committee member (Colorado State University. Libraries, 2025)
"Coaching for Wellness: A Guide to Mental Health and Substance Use Prevention in Women's Aesthetic Sports" is a comprehensive guide to the unique psychological issues faced by female athletes engaged in appearance-oriented sports, such as gymnastics, figure skating, and dance. This project aims to showcase the intersection of body image, performance pressure, and mental health symptoms that are ubiquitous but relatively ignored in aesthetic sports. Based on peer-reviewed research, I focused on four themes: substance abuse risk, eating disorders, relative energy deficiency in sports (RED-S), and external pressures through coaches, judges, and social media. To identify these focus areas, I analyzed recurring findings of mental health struggles across all aesthetic sports, then considered how systematic and cultural influences in aesthetic sports, like authoritarian-style coaching and the normalization of abuse, frame these problems. I discussed how mental health, trauma, and self-worth would present themselves while in the sport and after retirement. Next, I offered suggestions for better coaching training programs, athlete advocacy, and support for mental health. Ultimately, my research proves that mental health disorders that aesthetic athletes experience derive more from the culture and practices of aesthetic sport than athletes' experiences alone. With that, my thesis aims to inspire change around athlete well-being, identity, and systemic reform in aesthetic sports.
Colorado State University Department of Human Development and Family Studies.
Keywords: coaching; aesthetic athletes; aesthetic sports; eating disorder; relative energy deficiency in sports; substance abuse risk; abusive coaching; authoritarian-style coaching; coaching training programs; athlete advocacy; mental health support; gymnastics; figure skating; cheerleading; dancing